Disclosure of HEDGE instruments in non- financial companies of brazilian open capital (Revista Brasileira de Contabilidade e Gestão, 2018)
Hedge instruments are derivatives for protection against changes in the value of a hedged asset or liability. This research has as objective identified the lack of disclosure of hedge instruments in Brazilian non-financial publicly traded operations. For this, it was to analyze a sample composed by twenty non-financial e-mail, with greater total of the asset, listed in the Stock Exchange, Brazil, Stock Market, Balcony (B3). Presentations and Explanatory Reports, ii) Management Report, and iii) Reference Form. All documents used refer to the fiscal year ending in 2015. It is based on a checklist drawn up from CPC 40 (R1). The results show that there was a higher quality of information disclosure in the Financial Statements and Explanatory Notes related to hedging instruments, and that in the Management Report and Reference Form less items are disclosed, and these are predominantly qualitative In addition, from the analysis, it was possible to verify a tendency of the most powerful electronic systems of the type of hedge.
Keywords: Hedge; disclosure; financial instruments